Foundational sorghum kombucha research in swine: preference, cognition, and social testing - Nelson, Catherine E. (Kansas State University, 2024)
The use of swine has the potential to extend greatly beyond their current facets of utilization. The combined advancements in the methodology of behavioral collection and precision animal technology allow for the refinement of swine testing procedures regarding both efficiency and welfare. This thesis will introduce the development of procedures using a novel 3-pod maze to assess preference as well as the social impacts of an in-pen cognitive feeding test. Study 1 was conducted to measure pig preference for three different strains of fermented sorghum tea utilizing a three-pod radial maze. The first phase served to eliminate neophobia by acclimating in pairs with each bowl containing a control isocaloric solution of sugar water (positive control). The second phase conditioned the pigs individually using the positive control in one arm and distilled water (negative control) in the other two arms. The first experimental phase consisted of testing of testing the preference of three different versions of fermented sorghum tea. Each solution utilized a different strain of commercial sorghum: 1) Raw white, mild flavor profile, 2) Raw sumac, medium flavor profile, and 3) Roasted sumac, bold flavor profile. There was no clear preference between strain so in the second experimental phase the three teas were mixed and put into one pod on a rotation with the positive and negative control. Results showed that the 3Tea was the most desirable treatment as it had the highest consumption volume over the positive and negative controls. Total duration spent in the pod as well as duration of head over bowl behaviors was greatest for pods containing the 3Tea mixture and lowest for the negative control. In conclusion, the pigs preferred the 3Tea mixture over a sweetened water. This study provides evidence that pigs do not have a strong aversion to novel, sour, and bitter flavors as previously thought. Study 2 was conducted to test a prototype for an in-pen cognitive feeding task. Pigs were exposed to a cognition task that required them to push a series of paddles to receive a food reward. After a conditioning phase the pigs were randomly assigned a pattern for individual acquisition. The pattern consisted of either alternating, inner or outer paddles. Once the pigs completed the individual acquisition phase they were exposed to the test with the same pattern in pairs. Performance on the task was assessed through latency, duration, and frequency measures. The paired phases allowed for the analysis of social hierarchy and cooperation on task performance with an end goal of assessing if sociality and format impacted test performance. Social behaviors assessed included advance, retreat, and neutral. Frequency data for these social behaviors was utilized to calculate dominance indices and determine social status. Format did not have a significant impact on overall performance. However, the outside format had the highest rate of correct paddle contact leading to the extrapolation that it was the easiest for the pigs to uptake. Submissive pigs also had a significantly higher number of overall paddle presses as well as presses on the correct paddle, indication higher motivation and contrafreeloading status when faced with a cognitive task. Dominant pigs were likened to freeloaders as their higher social status was their main tool for meal acquisition. The results of these studies are assessed together through hematology results reported in the final chapter. Blood was collected from all pigs pre and post study. Dominant and submissive status assigned in study 2 was used to assess hematological differences between pen-mates and the potential health benefits of the fermented sorghum tea consumption. Dominant pigs showed higher levels of plasma glucose, triglycerides, and cholesterol. Dominant pigs also had higher overall body weight correlating with higher fat and inflammatory markers seen in the blood results. Despite an increase in size dominant pigs experienced a decrease in all of these variables post-study, rendering further investigation of the effects of fermented sorghum essential. The development of procedures for these studies will assist in the refinement and ultimate advancement of the role swine can play within the scientific community. A refinement of behavioral and cognitive data collection will create for more efficient and ethical housing of swine in production and translational studies. The methodology outlined within this thesis can be used as a guide for future studies assessing swine preference, cognition, and social hierarchy.
Keywords: Ossabaw; Sorghum; Preference; Cognition; Dominance; Behavior